PROMOTING LOCAL CULTURE BY USING 4-F APPROACH IN ELT CLASSROOM - Jenny Elvinna Manurung (Jurnal Dosen Universitas PGRI Palembang, 2016)
Abstract: English as a kind of language is a tool for people to communicate. At the same time, language is an important and prominent part of culture. This paper emphasizes the importance cultural awareness in preserving the local culture for English Language Teaching (English Language Teaching). By using 4F approach (Folk Dance, Festival, Fair and Food), the students can get cultural understanding in promoting the local culture itself. Through this approach, it also shapes the students’ character that involves internal changes in terms of attitudes and values. Increasing cultural awareness means to see aspects of cultural differences. Through this approach also develops the students’ motivation to promote their local culture. Keywords: local culture,4F approach, cultural awareness